Refusal Strategies Used By Multi-Nationality Students - Dewi, I Ar; Tantra, D.K.; Artini, L.P.; Ratminingsih, N.M. (JPI (Jurnal Pendidikan Indonesia), 2019)
This descriptive qualitative study was aimed at exploring refusal strategies used by the students of primary level of Gandhi Memorial Intercontinental School (GMIS) Bali in requesting, offering, inviting, and suggesting. The students being involved as the subject of this study were multi nationality (Indonesian, Indian, Russian, and Japanese) male and female students of the third, fourth and fifth grade which were determined using purposive sampling technique. Data collection was conducted through observation, recording, and note taking employing video recorder, camera, and field note as the instruments of the data collection. Data analysis in this study was done through four concurrent activities covering data collection, data reduction, data display, and conclusion. The result shows that, in context of request across nationalities, view from the frequency (percentage of refusals) it shows direct refusal is highly used by Russian while it is lowest used by Indonesian students. On the contrary indirect strategy is more often used by Indonesian students. while in context of refusing an offer. it reflects that Indonesian is mostly to refuse it in direct way but this is contrast with Russian who perform direct refusal in less frequent. This condition is in context of refusing in indirect way. the data reveals that Russian are more often to refuse the offering in indirect way while Indonesian is the lowest. In context of refusing invitation, nationality which is the highest used of direct refusal is Indian while nationality which was prefer to perform indirect refusal is Russian. In addition, in context of Suggestion, direct refusal is highly performed by Russian whereas indirect refusal is more often used by Japanese students.Â Â